Toward leader democracy [ - Pakulski, Jan , 1950-; Korosenyi, Andras (Key issues in modern sociology, 2012)
'Toward Leader Democracy' investigates how today's liberal democratic regimes are increasingly moving toward a pronounced focus on political leaders and their image, and explores the mechanics, evolution and implications of this phenomenon.